Medical And Biological Support For Young Athletes: Experience Of Sports Schools In Germany And Japan - Maprat Tairova (Euro Asian Journal Publishing, 2025)
Medical and biological support for young athletes plays a key role in ensuring their proper physical development, injury prevention, and the achievement of high sports performance. This issue is particularly relevant in the context of increasing training loads on children within the sports education system. This article examines the international experience of Germany and Japan in organizing medical and biological monitoring in sports schools. The main principles of these systems are analyzed, including regular testing, individual health records, the involvement of multidisciplinary teams, and the use of modern technologies for monitoring the condition of the body. The study is based on scientific publications, data from sports institutions, and official reports on the health of young athletes. The article also compares these practices with the current situation in Uzbekistan and identifies potential ways to integrate effective foreign approaches into the national sports medicine system. Emphasis is placed on the importance of a comprehensive approach that unites educators, coaches, and medical professionals into a unified mechanism for safeguarding the health of young athletes.
Keywords: sports medicine; young athletes; medical and biological support